The Education Effects in Personal Finance Management - Doda, Sanie (Mediterranean Journal of Social Sciences, 2013)
This research tries to identify the importance of the education in the well-managment of the personal finances. To improve yourinputs, it means to start a way toward a financiar fredoom. This doesn’t mean obligatorly to have a luxiory life, but to adaptefficient supplies to achive a given confort, assuring a more successful future. The education is one of the more importantelements, which push the development of the country. This is one of the basic reasons, why one of the strategic goals it is theliberalization of the teaching\education. The education is a potential variable, which has a large impact to take personalfinanciar decisions and in the managerial capability of the money, where the whole society aims a high financial turn into theinvestment into the high school\universities. It exists an unique connection between the education and the education’s resultsand these results into personal finances and the economical welfare, in general.